Clinical and radiologic characteristics of radiologically missed miliary tuberculosis. Issue 8 (26th February 2021) - Choe, Jooae; Jung, Kyung Hwa; Park, Joung-Ha; Kim, Sung-Han; Kim, Mi Young
Abstract : Abstract: While chest CT provides important clue for diagnosis of miliary tuberculosis (TB), patients are occasionally missed on initial CT, which might delay the diagnosis. This study was to evaluate the clinical and radiological characteristics of radiologically missed miliary TB. Total 117 adult patients with microbiologically confirmed miliary TB in an intermediate TB-burden country were included. 'Missed miliary TB' were defined as the case in which miliary TB was not mentioned as a differential diagnosis in the initial CT reading. Clinical characteristics and radiologic findings including the predominant nodule size, demarcation of miliary nodules and disease extent on CT were retrospectively evaluated. Findings were compared between the missed and non-missed miliary TB groups. Multivariable analyses were performed to determine independent risk factors of missed miliary TB. Of 117 patients with miliary TB, 13 (11.1%) were classified as missed miliary TB; these patients were significantly older than those with non-missed miliary TB (median age, 71 vs 57 years, P = .024). There was a significant diagnostic delay in the missed miliary TB group ( P < .001). On chest CT, patients with missed miliary TB had a higher prevalence of ill-defined nodules (84.6% vs 14.4%; P < .001), miliary nodule less than 2 mm showing granular appearance (69.2% vs 12.5%; P < .001), and subtle disease extent (less than 25% of whole lung field, 46.2% vs 8.7%; P < .001). Multivariable analysis revealed that only CT findings including ill-defined nodule (Odd ratios [OR], 15.64; P = .002) and miliary nodule less than 2 mm (OR, 10.08; P = .007) were independently associated with missed miliary TB. Approximately 10% of miliary TB could be missed on initial chest CT, resulting in a delayed diagnosis and treatment. Caution is required in patients with less typical CT findings showing ill-defined miliary nodules less than 2 mm showing granular appearance and follow-up CT might have a benefit.